Understanding the Impact of ErbB Activating Events and Signal Transduction on Antigen Processing and Presentation: MHC Expression as a Model - Kersh, Anna E.; Sasaki, Maiko; Cooper, Lee A.; Kissick, Haydn T.; Pollack, Brian P. (Frontiers in Pharmacology, 2016)
Advances in molecular pathology have changed the landscape of oncology. The ability to interrogate tissue samples for oncogene amplification, driver mutations, and other molecular alterations provides clinicians with an enormous level of detail about their patient’s cancer. In some cases, this information informs treatment decisions, especially those related to targeted anti-cancer therapies. However, in terms of immune-based therapies, it is less clear how to use such information. Likewise, despite studies demonstrating the pivotal role of neoantigens in predicting responsiveness to immune checkpoint blockade, it is not known if the expression of neoantigens impacts the response to targeted therapies despite a growing recognition of their diverse effects on immunity. To realize the promise of ‘personalized medicine’, it will be important to develop a more integrated understanding of the relationships between oncogenic events and processes governing anti-tumor immunity. One area of investigation to explore such relationships centers on defining how ErbB/HER activation and signal transduction influences antigen processing and presentation.